The microbiota in the development of colitis due to Clostridium difficile infection - Young, Vincent (Henry Stewart Talks, 2011)
C. difficile and the antibiotic-associated colitis, Changes in the microbiota due to antibiotics predisposed to C. difficile infection, Use of culture-independent techniques to study the gut microbiota, Antibiotics can have reproducible effects on the gut microbiota, Animal models and human studies provide insight into the role of the gut microbiota in mediating colonization resistance against C. difficile infection